Restorative Justice as an Instrument for Implementing the Principle of Dominus Litis in Resolving Narcotics Cases: A New Paradigm for Humanistic Prosecution - Mulyadi Alrianto Tajuddin (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
This article examines the integration of the dominus litis principle with the restorative justice approach in the prosecution of narcotics cases in Indonesia. The study highlights the persistent reliance on retributive justice, resulting in overcrowded prisons and limited rehabilitation for drug users. Using a normative juridical method with statutory and conceptual approaches, this research analyzes relevant legal frameworks including the Narcotics Law and prosecutorial regulations. Findings show that although restorative justice has normative support through legislation and prosecutorial guidelines, its implementation remains limited due to institutional inertia, lack of technical provisions, and weak prosecutorial discretion. The dominus litis principle, which grants public prosecutors authority over case management, is underutilized as a tool to shift from punitive to rehabilitative approaches. The article proposes a humanistic prosecution model grounded in restorative values and structured prosecutorial discretion. This model emphasizes selective case processing, interdisciplinary assessments, and integrated institutional cooperation. It aims to transform drug case handling from a punitive paradigm to a rehabilitative and socially responsive justice framework. The study recommends the issuance of technical guidelines by the Attorney General to facilitate this shift and enhance prosecutorial legitimacy. This research contributes to the discourse on progressive criminal law reform by offering a normative foundation for sustainable and ethical prosecution policies in narcotics cases.